Life history and ecology of harbour porpoises ( Phocoena phocoena ) from West Greenland - C Lockyer; M P Heide-Jørgensen; J Jensen; M J Walton (NAMMCO Scientific Publications, 2003)
During 1988, 1989 and 1995, 187 harbour porpoises (Phocoena phocoena) were sampled from the catches off West Greenland. The samples were taken in 3 areas between 62° N and 70° N: northerly (n=134, Maniitsoq and locations Kangaamiut, Qeqertarsuaq and Qasigiannguit further north), southerly (n=30, Nuuk) and southernmost (n=23, Paamiut). A suite of biological measurements and data were collected from these samples. Comparison of age and length distributions between years and areas indicated that while there were no statistical differences between the Maniitsoq and northerly samples in different years, the southerly Nuuk and Paamiut samples were biased to younger age classes. Application of the Gompertz growth model to length and weight at age data indicated an asymptotic length of 154 cm in females and 143 cm in males with weights of 64 kg and 52 kg respectively. A number of correlations were observed between length, midgirth(G3), body and blubber weights and blubber thickness. Indicators of body condition showed that overall pregnant females were fattest but that blubber thickness was greatest in juveniles. The blubber lipid content was generally 92-95% wet weight of tissue. Stomach content analysis for 92 animals indicated regional differences, although capelin (Mallotus villosus) was predominant in all samples. The presence of fish, squid and crustaceans indicated opportunistic feeding. Females ovulated from age 3-4 years at a length of about 140 cm; combined testis weights >200 g indicated maturation in males from age 2 years upwards at a length >125 cm. Several small embryos were found, consistent with a mating season in late summer. Testis hypertrophy in August also supported a late summer breeding. Analysis of ovarian corpora indicated annual ovulation. Certain biological parameters, including body condition indicators, indicate differences between WestGreenland and eastern North Atlantic populations that agree with published genetic findings.